BIODELIGNIFICATION OF AGRO-INDUSTRIAL WASTE AS THE SUBSTRATE TO PRODUCE LACCASE ENZYME FROM TRAMETES VERSICOLOR - Perdani, Meka Saima; Malisi, Sibro; Putri, Dwini Normayulisa; Margaretha, Grace; Hermansyah, Heri (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2024)
Agro-industrial waste in Indonesia is a significant problem for the environment. Optimization of agro-industrial waste utilization is an exciting thing to be researched further. This study aims to utilize agro-industrial waste to optimize laccase enzyme production. The agro-industrial waste used is in the form of bagasse, rice straw, and corn stalks. The waste is used as biomass and treated to extract cellulose through bio-delignification. Cellulose serves as a substrate substance in the production of laccase enzymes. Laccase enzymes can be applied as a biocatalyst in the environmental, pharmaceutical, and chemical industries. Cellulose from agroindustry waste was synthesized by heat treatment using steam explosion with the operation conditions 200°C and 10 bar for 10 minutes. The production of laccase enzymes was done using the green technology submerged fermentation method for 32 hours at 25°C. The optimal result in producing laccase enzyme is using substrate from corn stalks and adding nutrients with an activity value of 25.46 U/mL. The reaction kinetics of laccase enzyme and commercial enzyme against 0.1 M substrate were modelled using the Euler method, and the k value was 2x10-4 min-1 (crude laccase) and 1.9x10-2 min-1 (commercial laccase).